Inattentive Perception, Time, and the Incomprehensibility of Consciousness - Krüger, Jürgen (Frontiers in Psychology, 2022)
Cerebral energy supply is insufficient to support continuous neuronal processing of the plethora of time-constant objects that we are aware of. As a result, the brain is forced to limit processing resources to (the most relevant) cases of change. The neuronally generated world is thus temporally discontinuous. This parallels the fact that, in all relevant microscopic fundamental equations of nature, temporal change plays a dominant role. When a scientist calculates a ‘solution’ to such an equation, integration over time is an essential step. The present Hypothesis expresses that the step from neuronal activity to phenomenal content of consciousness is reflective of a (phenomenal) ‘solution’: the main source of the incomprehensibility of consciousness is proposed to result from the introduction of phenomenal time-constant entities. These are ‘filled-in’ via integration, even though neuronal data only exists for changes to these entities. In this way, a temporally continuous picture of the world phenomenally appears. Qualia are ‘initial conditions’, which are required for integration and cannot be deduced from present data. Phenomenal ‘identity’ (versus ‘high similarity’) is related to qualia. Inattentive visual perception, which is only rarely investigated, offers insights into these relationships. Introspectively, unattended vision appears rich because percepts are cumulated over long time spans, whereas attentive perception relies purely on present neuronal signals. The present Hypothesis is that a brief neuronal activity can signify long-lasting and constant phenomenal content of consciousness. Experimental support is presented that comes from discrepancies between neuronal activity and perception: transient neuronal responses to sustained stimuli, ‘filling-in’, change blindness, identity versus close resemblance.